Internalisasi Corporate Value Dalam Pembinaan Moral Rohani Pegawai DIRJEN Pajak Jember - Muhammad Habibi Hamzah; Raadliyatush Shalihah (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This activity was carried out at the Jember Tax Directorate in collaboration with a committee of employees packaged in an event for the Internalization of Corporate Values to improve employee performance, especially from a spiritual aspect, as this aspect is considered to have a significant influence on the strengthening and enhancement of employees' core values. The activity consists of two stages: material delivery and evaluation. In the evaluation stage, this is conducted in two ways: Q&A and reviewing the material that has been delivered. As a result of this activity, employees were able to absorb the material presented well and are expected to implement it in their work in the relevant agency.